THE ACTIONS UNDERTAKEN BY HORTENSIA COSMA-GOGA DURING HER TIME AS AN IMMIGRANT IN ITALY (1917 - 1919) FOR THE ESTABLISHMENT AND THE INTERNATIONAL RECOGNITION OF GREATER ROMANIA - Mihai D. DRECIN (Annals: Series on History and Archaeology (Academy of Romanian Scientists))
In January 1917, Maria and Partenie Cosma emigrated to Italy accompanied by their daughters, Lucia and Hortensia, in the context of the latest developments in the Romanian war front. From there, Hortensia Cosma-Goga, would inform her husband - who was a part of the Romanian political elite preparing Romania s participation in the Peace Conference of the pro-Romanian, pro-Hungarian, and pro-Serbian political views concerning the future of Greater Romania s western border.